Analisis Pengaruh Gaya Belajar Terhadap Hasil Belajar Pada Materi Ikatan Kimia - Ayu Maulida; Farah Erika; Yuli Hartati (Lembaga Bale Literasi, 2026)
Differences in students’ learning styles often affect learning outcomes, particularly in abstract and conceptual subjects such as chemical bonding. This study aims to examine the influence of learning styles on the learning outcomes of Grade X students in the topic of chemical bonding. A comparative quantitative approach was employed using an ex post facto design. The sample consisted of 75 students selected through a saturated sampling technique. Data were collected through a learning style identification questionnaire and documentation of daily test scores. Data analysis was conducted using a One-Way ANOVA test followed by the Tukey HSD test. The results showed that learning styles had a significant effect on learning outcomes (p = 0.027), with students with an auditory learning style achieving the highest average scores. Significant differences were found between auditory and kinesthetic groups, as well as between visual and auditory groups. These findings emphasize the importance of aligning instructional strategies with students’ learning styles to enhance learning effectiveness. Observations also revealed that kinesthetic learners showed lower engagement, indicating the need for more active and exploratory learning approaches. This study recommends that teachers map students’ learning styles as a basis for designing responsive and adaptive instruction, especially for complex chemistry topics.